Calibration of Audio-Video Sensors for Multi-Modal Event Indexing - Kϋhnapfel, Thorsten; Tan, Tele; Venkatesh, Svetha (IEEE Computer Society Conference Publishing Services, 2007)
This paper addresses the coordinated use of video and audio cues to capture and index surveillance events with multimodal labels. The focus of this paper is the development of a joint-sensor calibration technique that uses audio-visual observations to improve the calibration process. One significant feature of this approach is the ability to continuously check and update the calibration status of the sensor suite, making it resilient to independent drift in the individual sensors. We present scenarios in which this system is used to enhance surveillance.